Access to Justice within Administrative Proceedings of Ukraine: Modern Realities and European Experience - Krupchan, O.; Salmanova, O. Yu.; Салманова, О. Ю.; Makarenko, N.; Paskar, A.; Yatskovyna, V.; Olena Salmanova (Cuestiones Políticas. – 2023. – Vol. 41, № 77. – P. 103-115, 2023)
The purpose of the article was to analyze the availability of justice within the Ukrainian administrative judicial system, examining its specific features in terms of martial law and the possibilities of its improvement, due to the implementation of European standards in Ukrainian legislation. The research methods used were: monographic analysis, analysis and synthesis, systemic, generalization, forecasting, etc. It has been found that the principle of access to justice is manifested in the ability of a person to receive unimpeded judicial protection and to apply for judicial protection of one’s rights. It has been emphasized that the reform of the judicial procedure in the resolution of administrative disputes requires the earlier introduction of digital technologies and Artificial Intelligence technologies. This will help to ease the burden on the court system and judges, speed up the time of hearing court cases, reduce the costs of their storage and archiving, simplify the presentation of statements and evidence in court, etc. It is concluded that the implementation of the European standards of the administrative process will lead to ensuring the appropriate degree of access to justice in Ukraine and increase public confidence in the judiciary.

Метою статті було проаналізувати доступність правосуддя в системі адміністративного судочинства України, дослідивши його особливості в умовах воєнного стану та можливості його вдосконалення, завдяки імплементації європейських стандартів в українське законодавство. Використані методи дослідження: монографічний аналіз, аналіз і синтез, системний, узагальнення, прогнозування тощо. Встановлено, що принцип доступу до правосуддя проявляється у можливості особи отримати безперешкодний судовий захист та звернутися до суду з позовом. захист своїх прав. Наголошено, що реформування судочинства у вирішенні адміністративних спорів вимагає більш раннього впровадження цифрових технологій та технологій штучного інтелекту. Це дозволить зменшити навантаження на судову систему та суддів, прискорити час розгляду судових справ, зменшити витрати на їх зберігання та архівування, спростити подання заяв і доказів у суді тощо. Зроблено висновок про реалізацію європейських стандартів адміністративного процесу призведе до забезпечення належного рівня доступу до правосуддя в Україні та підвищення довіри суспільства до судової влади.

Целью статьи было проанализировать доступность правосудия в системе административного судопроизводства Украины, исследовав его особенности в условиях военного положения и возможности его усовершенствования благодаря имплементации европейских стандартов в украинское законодательство.
Acceso a la justicia dentro de los procedimientos administrativos de Ucrania: realidades modernas y experiencia europea
Keywords: Україна; publikatsii u WoS; Ukraine; right to a fair trial; access to justice; administrative justice; information technologies; international standards of justice; право на справедливий суд; доступ до правосуддя; адміністративна юстиція; інформаційні технології; міжнародні стандарти правосуддя; право на справедливое судебное разбирательство; доступ к правосудию; административное правосудие; информационные технологии; международные стандарты правосудия